Mechanisms and consequences of leukocyte-endothelial interaction. - Harlan, J. M. (1991)
Leukocyte adhesion to endothelium is a critical event in host defense against microorganisms and in the repair of tissue damage. Under some circumstances, however, altered leukocyte-endothelial interactions may contribute to the pathogenesis of inflammatory and immune diseases. In a number of experimental models, the inhibition of leukocyte adherence to endothelium substantially reduces vascular and tissue injury. Antiadhesion therapy may represent a novel approach to the treatment of a wide spectrum of clinical disorders.